Thermal Diffusion Characteristics in Permafrost during the Exploitation of Gas Hydrate. (10th March 2021) - Wei, Yusen; Xiong, Youming; Liu, Zhiqiang; Lu, Jingsheng
Abstract : Methane hydrate is the vast potential resources of natural gas in the permafrost and marine areas. Due to the occurrence of phase transition, the gas hydrate is dissociated into gas and water and absorbs lots of heat. The incomprehensive knowledge of endothermic reaction in permafrost sediments still restricted the production efficiency of hydrate commercial development. This endothermic reaction leads to a complex thermal diffusion in permafrost, which directly influences the phase transition in turn. In this research, the heat during the exploitation is transferred in two forms (specific heat and latent heat). Besides, the melting point is not constant but depends on the pore size of the reservoir rock. According to these features, a thermal diffusion model with phase transition is established. To calculate the governing equation, the pore size distribution is obtained by using the nuclear magnetic resonance (NMR) method. The heating tests are conducted and simulated to calibrate the coefficient (i.e., transverse surface relaxivity) of NMR. Then, the temperature field evolution of the hydrate reservoir during the exploitation is simulated by using the calibrated values. The results show that the temperature curves have a typical plateau related to the pore size distribution, which is effective to obtain the surface relaxivity. The heat transfer is remarkably limited by the endothermic effect of the phase transition. The hydrate recovery efficiency may depend largely on the heating capacity of the engineering operation and the rate of gas production. Compared to the conventional petroleum industry, it is significant to control the maximum temperature and temperature distribution in engineering operations during hydrate development. This research on the temperature behavior during onshore permafrost hydrate production could provide the theoretical support to control heat behavior of offshore hydrate production.